A new species of Agroeca Westring, 1861 from Navarra, Spain (Araneae: Liocranidae) - de Biurrun, Gabriel; Barrientos, José Antonio; Baquero, Enrique (Zootaxa, 2021)
A new spider species belonging to the genus Agroeca Westring, 1861 is described. Agroeca istia sp. n. has been collected in southern Navarra, Spain. The description is based on 21 individuals of both sexes, present throughout the year on the ground of pine forests and surrounding low vegetation of the Natural Reserve Vedado de Eguaras.